Kedudukan Hadith Ḍa‘īf dalam Keputusan Baḥth al-Masā’il Nahdatul Ulama: Satu Analisis Kritis: The Position of Weak Hadith in the Resolution of Baḥth al-Masā’il by Nahdatul Ulama: A Critical Analysis - Ahmad Shah, Faisal; Haba, Badaruddin (Jurnal Usuluddin, 2020)
Baḥth al-Masā’il is one of the religious discussion forums of the Nahdatul Ulama organization to respond to current issues that arise in people's lives. The decision of Baḥth al-Masā’il to be decided can be considered as a ruling that guides the members of Nahdatul Ulama. Hadith is the second major source after the Quran for the Nahdatul Ulama in establishing the law. This study aims to analyze the hadiths that NU argues to identify the quality and strength of its arguments. From the forty hadiths analyzed, there are five weak hadiths and one hadith ‘ḍa‘īf jiddan’ which all deal with the laws. This shows one weakness in arguing. Hopefully this study can contribute to NU to make improvements of the methodology of hadith arguing.